The influence of financial knowledge, education level, and personality on financial management behavior among MSME owners in Kampung Kue Rungkut, Surabaya - Ismi Dwi Safitri; Nurjanti Takarini (Journal of Management Small and Medium Enterprises (SMEs), 2026)
Financial management practices are widely recognized as a critical determinant of the sustainability and growth of micro, small, and medium enterprises (MSMEs). However, many MSMEs continue to experience challenges in implementing effective financial management practices, particularly in emerging economies. This study examines the effects of personality, education level, and financial knowledge on the financial management practices of MSME owners in Kampung Kue Rungkut, Surabaya, Indonesia. A quantitative research design was employed using a census approach involving all 59 MSMEs operating in the study area. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that education level and financial knowledge positively and significantly influence financial management practices, suggesting that MSME owners with higher educational attainment and greater financial literacy are more likely to adopt sound financial practices. In addition, personality is found to play an important role in shaping financial management behavior. These results underscore the importance of enhancing MSME owners’ financial capabilities and fostering positive behavioral attributes to support business sustainability. The study contributes to the MSME and financial management literature by providing empirical evidence from a community-based MSME cluster in Indonesia and offers practical implications for policymakers and development agencies seeking to strengthen MSME resilience through targeted education and financial literacy initiatives. Keywords: Educational Level; Financial Knowledge; Financial Management Behavior; MSMEs; Personality